The use of mobile technology to improve service delivery in the hospitality industry: a case of restaurants in Kenya - Ogolla, Arnold Nyochieng (Strathmore University, 2013)
The research takes a look at the restaurant industry in Kenya as well as the trends in the mobile industry. It then looks into how we can leverage the mobile industry to better the hospitality industry.The research determines that the communication channel between restaurant owners and their customers is weak and needs to be improved. A mobile solution “Wapi” is proposed to help improve service delivery in the hospitality industry. “Wapi” is a mobile solution that enables users to search for their favourite restaurants and view the prices of the meals served by these restaurants. It has two interfaces: The restaurant management web application and The restaurant locator mobile application. The solution attempts to provide reliable and up to date information on restaurants to users in a manner that is very easy to access at all times. The system is designed developed and tested by a subject matter expert during the research period. The research concludes that the mobile solution would add value to the communication channel between the restaurant owner and customer. It also concludes that the application is ready for the market as it passed all the required tests carried out. The research recommends further work to developing more modules for the system as well as a follow up research to test on the effectiveness of the system.
Thesis submitted to the Faculty of Information Technology in partial fulfillment of the requirements for the award of a Master of Science Telecommunications Innovation and Development of Strathmore University